Working capacity of patients with Parkinson's disease – A systematic review. (June 2016) - Koerts, Janneke; König, Miriam; Tucha, Lara; Tucha, Oliver
Abstract: Introduction: Parkinson's disease (PD) is characterized by motor and non-motor symptoms and has a median age-of-onset around 55 years. Many PD patients are thus diagnosed before reaching retirement age and it is likely that they are confronted with a reduced working capacity or loss of employment. This systematic literature review gives an overview of the research conducted on work capacity in PD. Methods: A systematic literature search was performed in PsycINFO and PubMed (Keywords: "Parkinson" or "Parkinson's disease" combined with "employment", "work", "working", "retire" or "retirement"). Results: Thirteen studies were identified and showed that PD patients retired 4–7 years earlier than the general population. Furthermore, 23%–75% of patients report that they retired early because of PD and slowness and fatigue were reported as the most debilitating symptoms in relation to working capacity. Early retirement of PD patients is associated with high societal costs and a high loss of individual lifetime earnings. Although many employed PD patients asked for adjustments at their workplace, their employers did not always support these. Conclusions: PD has a detrimental effect on working capacity and is associated with high costs. Employed PD patients do not, however, always receive the support they need. It is therefore very relevant that employers and patients are informed about strategies and techniques developed for counteracting symptoms of PD which might support patients to stay in the workforce for a longer period of time. Highlights: PD has a detrimental effect on working capacity of patients. Early retirement of PD patients is associated with high societal costs. Both motor and non-motor symptoms of PD contribute to a reduced working capacity. Employed PD patients ask for workplace adjustments; these are not always supported.